Comprehensive Analysis to Identify SPP1 as a Prognostic Biomarker in Cervical Cancer - Zhao, Kaidi; Ma, Zhou; Zhang, Wei (Frontiers in Genetics, 2022)
Background: SPP1, Secreted phosphoprotein 1, is a member of the small integrin binding ligand N-linked glycoproteins (SIBLINGs) family. Previous studies have proven SPP1 overexpressed in a variety of cancers and can be identified as a prognostic factor. While, no literature has explored the function and carcinogenic mechanism of SPP1 in cervical cancer. Methods: We aimed to demonstrate the relationship between SPP1 expression and pan-cancer using The Cancer Genome Atlas (TCGA) database. Next, we validated SPP1 expression of cervical cancer in GEO (Gene Expression Omnibus) database, including GSE7803, GSE63514 and GSE9750. ROC (Receiver operating characteristic) curve was used to evaluate the feasibility of SPP1 as a differentiating factor by AUC (area under curve) score. Cox regression and logistic regression were performed to evaluate factors associated with prognosis. SPP1-binding proteins network was built by STRING tool. Enrichment analysis by R package “clusterProfiler was used to explore potential function of SPP1. Single sample GSEA (ssGSEA) method from R package GSVA and TIMER database were used to investigate the association between immune infiltration level and SPP1 expression in cervical cancer. Results: Pan-cancer data analysis showed SPP1 expression was higher in most cancer types, including cervical cancer. And we got the same result in GEO database. ROC curve suggested SPP1 could be a potential diagnostic biomarker (AUC=0.877). High SPP1 expression was associated with poorer OS (Overall survival) (P=0.032). Further enrichment and immune infiltration analysis revealed that high SPP1 expression was correlated with regulating the infiltration level of neutrophil cells and some immune cell types, including macrophage and DC. Conclusions: SPP1 expression was higher in cervical cancer tissues compared with normal cervical epithelial. It was significantly associated with poor prognosis and immune cell infiltration. Thus, SPP1 may become a promising prognostic biomarker for cervical cancer patients.